The problem of medium access control in wireless sensor networks. - Sagduyu, Y.E (IEEE Wireless communications)
In this article we revisit the problem of scheduled access through a detailed foray into the questions of energy consumption and throughput for MAC protocols in wireless sensor networks. We consider a static network model that rules out simultaneous transmission and reception by any sensor node and consequently requires partitioning of nodes into disjoint sets of transmitters and receivers at any time instant. Under the assumption of circular transmission (reception) ranges with sharp boundaries, a greedy receiver activation heuristic is developed relying on the network connectivity map to determine distinct receiver groups to be activated within disjoint time intervals. To conserve limited energy resources in sensor networks, the time allocation to each receiver group is based on the residual battery energy available at the respective transmitters. Upon activating each receiver group separately, the additional time-division mechanism of group TDMA is imposed to schedule transmissions interfering at the non-intended destinations within separate fractions of time in order to preserve the reliable feedback information. The two-layered time-division structure of receiver activation and group TDMA algorithms offers distributed and polynomial-time solutions (as required by autonomous sensor networks) to the problems of link scheduling as well as energy and throughput-efficient resource allocation in wireless access. The associated synchronization and overhead issues are not considered in this article.